Content and Language Integrated Learning in Argentina 2008 - 2011 - Dario Luis Banegas (Universidad de La Sabana, 2011)
The incorporation of content, whether it is L1-curriculum based or from general knowledge of the world, is not innovative in English Language Teaching. However, CLIL as an umbrella approach has spread the interest in learning English through non-language subject matter to non-European contexts. In this review article, I analyse the development of the Argentinean interest in CLIL from two conference proceedings from the years 2008 and 2009, and a more institutional curriculum-based implementation conceived in 2010-2011. While CLIL in Argentina started as a bottom-up approach because teachers and learners wanted to integrate content and language, now CLIL may spread because official curricula determine so.